APPLICATION OF ORGANIC ADDITIVES AS VOLTAGE ENHANCERS FOR VERMICOMPOST-DERIVED BIO-BATTERY - YUN HOCK, PHUA (IRC, 2017)
A bio-battery which is powered by organic compounds provides a clean alternative renewable power source. Huge amount of green wastes around Universiti Teknologi PETRONAS (UTP) campus such as fallen leaves and grass clippings provides an opportunity for waste conversion into value-added products using an eco-friendly composting method called vermicomposting where locally abundant earthworms are added to speed up the breakdown the organic wastes into vermicompost. Recent studies revealed the potential of vermicompost to be used as green electrolyte of bio-battery instead of being solely used as fertilizer. However, the voltage produced from bio-battery is found typically lower and less stable than conventional batteries. The main goal of this research work is therefore to enhance the voltage generation of bio-battery derived from UTP vermicomposts. As a start, good quality vermicompost was produced from available green wastes in UTP compound at optimum carbon-to-nitrogen (C:N) ratio of 30. Next, the humic acid and fulvic acid were be extracted from the vermicompost to be used as the bio-battery’s electrolytes. Different organic additives were added into the electrolyte to determine their suitability as voltage enhancers via voltage profiling. Compost quality was established by final C:N ratio, humic and fulvic acid yield and moisture content analysis in comparison to commercial vermicompost. Key highlights of the project include vermicompost reached maturation on day 41, mass reduction of 18%, and humic and fulvic acid yields at 3.41% and 0.38%. The highest voltage recorded was 0.62 V for humic acid electrolyte with fruit enzyme additive. This approach has multi-fold benefits of cutting down labour requirement, promoting eco-friendly waste management and generating value-added products from waste.